Linking environmental regulation and economic growth through technological innovation and resource consumption: Analysis of spatial interaction patterns of urban agglomerations. (May 2020) - Cao, Yu; Wan, Ningna; Zhang, Haiyong; Zhang, Xiaoling; Zhou, Qian
Highlights: Verify the inverted-U between environmental regulation and economic growth. Economic development of the Yangtze River Delta shows a good interactive pattern. Environmental regulation and economic development display good interaction pattern. The impact mechanisms are the innovation and the resource consumption effects. The economic integration of the Yangtze River Delta is in an orderly manner. Abstract: The Yangtze River Delta region is a representative region for the development of China's urban agglomerations. This study explores the inverted U-shaped relationship between environmental regulation and economic growth in the Yangtze River Delta region during 2002–2010 using the spatial panel data model. After the introduction of instrumental variables, the U-shaped curve is still robust, which is the theoretical value of this paper. The research verifies that technological innovation and resource consumption are important mechanisms for environmental regulation to influence economic growth. Cities in the Yangtze River Delta region have good interaction patterns in environmental regulation, economic development, technological innovation and resource consumption. Economic integration development is at a good level and can provide valuable experience for the development of other urban agglomerations.